Privy to the Dead. - Connolly, Sheila (Connolly, Sheila. Museum mysteries., 2015)
When a construction worker who found a curious metal object while excavating an old privy in the museum's basement is murdered, Nell Pratt, president of the Pennsylvania Antiquarian Society, must unearth a mystery with ties to the past and the present to stop a killer.